2009
DOI: 10.1007/s11120-009-9442-2
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to magnetic resonance methods in photosynthesis

Abstract: Electron paramagnetic resonance (EPR) and, more recently, solid-state nuclear magnetic resonance (NMR) have been employed to study photosynthetic processes, primarily related to the light-induced charge separation. Information obtained on the electronic structure, the relative orientation of the cofactors, and the changes in structure during these reactions should help to understand the efficiency of light-induced charge separation. A short introduction to the observables derived from magnetic resonance experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is shown that three atoms (D···O • –N) lie on the same plane. Here, we used the following assumption: the g tensor of TEMPO-MI is same with that of other TEMPO derivative compounds; the g zz axis is parallel to the p z orbital of nitroxide radical and the g xx axis is parallel to the N–O • direction. , Interestingly, 2 H ENDOR spectra of 1 , 2 , and 3 are similar and are not affected by the concentration of salt (Figure S6). This phenomenon may imply that the hydrogen bonding networks are unchanged by the degree of self-assembly events and are very well conserved at the initial stage of self-assembly.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is shown that three atoms (D···O • –N) lie on the same plane. Here, we used the following assumption: the g tensor of TEMPO-MI is same with that of other TEMPO derivative compounds; the g zz axis is parallel to the p z orbital of nitroxide radical and the g xx axis is parallel to the N–O • direction. , Interestingly, 2 H ENDOR spectra of 1 , 2 , and 3 are similar and are not affected by the concentration of salt (Figure S6). This phenomenon may imply that the hydrogen bonding networks are unchanged by the degree of self-assembly events and are very well conserved at the initial stage of self-assembly.…”
Section: Results and Discussionmentioning
confidence: 99%
“…24 Protonophores assist in dissipating this membrane potential barrier. 25 Electron paramagnetic resonance studies of PSI 26,27 had indirectly implied the probable influence of SMF on the cyclic electron flow around PSI. [28][29][30] PSI is one of two multi-subunit pigment-protein complexes embedded in the thylakoids of chloroplast and the inner membranes of cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%